1999
DOI: 10.2169/internalmedicine.38.436
|View full text |Cite
|
Sign up to set email alerts
|

Vasospastic Angina Likely Related to Cisplatin-containing Chemotherapy and Thoracic Irradiation for Lung Cancer.

Abstract: Vasospastic angina is rarely observed during cancer treatment. The present report describes two males with lung cancer, aged 73 and 61, who developed vasospastic angina during combination treatment of cisplatin-containing chemotherapy and thoracic irradiation. As both patients have smokedand their ages are typical for patients with coronary artery disease, such events may be incidental. However, oncologists should be aware of the possible development of myocardial ischemia during or following administration of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…Cancer chemotherapy has also been associated with vasospastic angina [28][29][30][31][32][33]. Indeed our patient, who had previously been reported allergic to iodinated contrast media, developed allergic angina and coronary vasospasm after therapy with cisplatin and cyclophosphamide.…”
Section: Discussionmentioning
confidence: 53%
“…Cancer chemotherapy has also been associated with vasospastic angina [28][29][30][31][32][33]. Indeed our patient, who had previously been reported allergic to iodinated contrast media, developed allergic angina and coronary vasospasm after therapy with cisplatin and cyclophosphamide.…”
Section: Discussionmentioning
confidence: 53%
“…Hanchate et al reported a case which cisplatin‐induced acute myocardial infarction and dyslipidemia. Fukuda et al reported case series that vasospastic angina was likely caused by cisplatin‐containing chemotherapy and thoracic irradiation for lung cancer. Acute vascular toxicity due to cisplatin can occur during or soon after chemotherapy and has been attributed to vasospastic angina .…”
Section: Discussionmentioning
confidence: 81%
“…Early case reports revealed that cisplatin may cause acute myocardial infarction or coronary vasospasm . Hanchate et al reported a case which cisplatin‐induced acute myocardial infarction and dyslipidemia.…”
Section: Discussionmentioning
confidence: 99%
“…Whether nitrogen monoxide, vascular endothelial growth factor receptor interactions, or Rho kinase activation may be involved in the molecular steps induced by platinum-derived chemotherapeutics and especially by oxaliplatin, has not yet been established [20,21]. Additionally, platinum-based agents exert an activating effect on thrombocytes alleviating coagulation and release of thromboxan A2, which in turn may provoke vasoconstriction in the smooth muscle cells of the endothelium [15,22]. However, ongoing research is needed to clarify the pathomechanisms of oxaliplatin potentially causing coronary vasospasm.…”
Section: Discussionmentioning
confidence: 99%